Mapping of Malaria Receptivity Areas in Buton Regency, Southeast Sulawesi Province - Afsahyana Afsahyana; Mustaman; Nurhayati; Naswir (Universitas Mandala Waluya, 2021)
Malaria is an acute and chronic infectious disease caused by Plasmodium infection that attacks erythrocytes and is characterized by the discovery of asexual forms in the blood with symptoms of fever, chills, anemia and enlarged spleen. Buton Regency is a district with an Annual Parasite Incidence (API) that is less than 1 per 1000 population for 4 consecutive years and is a low endemic area. This study aims to determine the level of receptivity of malaria transmission areas in Buton Regency, Southeast Sulawesi Province. This type of research is descriptive observational with a cross sectional study approach. The results showed that there were 3 species of Anopheles identified in adult mosquitoes, namely An.Minimus, An.Indifinitus and An.Kochi. Habitat Index (HI) of Anopheles vector, sp > 1, breeding places for Anopheles vector wallows, rivers, ditches, ponds, rivers, swamps and rice fields with the characteristics of the presence of temporary and clear water, moss and mud, with a pH of 6 on a scale 6-6.5 and zero salinity. Vector confirmation by PCR is negative for all species. It was concluded that the level of malaria receptivity in Buton Regency, especially in the Village of Face Jaya, was at a moderate receptivity level.